Dinamika Politik Hukum dalam Peradilan Islam: Tantangan Implementasi Keadilan Substantif di Era Modern - Abdul Aziz Anwar; Kurniati Kurniati; Zulhas’ari Mustafa (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The modern era brings new complexities to the world of justice, thus facing new challenges that tend to be positivistic. In this case, substantive justice prioritizes the content and value of truth over the procedures of legal texts. This study aims to analyze and identify challenges in its implementation in the modern era. The form of substantive justice in this study is understood as the judge's effort to penetrate the rigidity of legal texts in order to achieve material truth and real benefits. Using normative legal research methods, the results show that the implementation of substantive justice faces significant challenges in the form of the dominance of judicial bureaucratic standardization, as well as limitations in the integrity and courage of judges' ijtihad. In the digital and globalized era, these challenges are further complicated by the emergence of new disputes that have not been explicitly accommodated in formal regulations. This study concludes that strengthening the intellectual and moral capacity of judges, as well as reorienting legal education beyond text-based to values-based, are key to ensuring that the judiciary produces decisions not only with legal certainty but also decisions that foster a sense of justice in society and protect rights, thus becoming solutions for justice and the benefit of the people.